Analysis of microporous layer characteristics of the anode for high-temperature polymer electrolyte membrane fuel cell. (1st August 2022) - Chun, Hyunsoo; Jung, Hyeon-Seung; Kim, Do-Hyung; Kim, Dong Hee; Pak, Chanho
Abstract: Four commercial gas diffusion layers (GDLs) are applied to high-temperature polymer electrolyte fuel cell anodes to investigate the relationship between microporous layer (MPL) properties and the performance of membrane electrode assembly. Subsequently, the physical properties such as the crack area and porosity of the MPL are analyzed via various methods. It is found that the capillary pressure of phosphoric acid (PA) from several theories is inversely related to the mass transfer capability (MTC) of the MPL. Finally, a new transport property named PA MTC of the MPL is proposed using the PA capillary pressure and MTC in MPL. The results indicate that the voltage at both low and high current densities increases separately as the PA MTC in the MPL adjusts to 0.5 MPa mm - 1 . Subsequently, the voltage beyond 0.5 MPa mm - 1 increases in low current density contrary to the voltage at a high current density. Highlights: Anode GDLs are applied to high-temperature polymer electrolyte fuel cell. The crack area of MPL has a high correlation with its porosity. A new transport property called PA MTC in the MPL is proposed.